Solid accumulation, a critical aspect regarding intensive aquaculture systems: alternatives for sustainable management (Orinoquia, 2022)
Maintaining water quality in intensive aquaculture production systems has becomea challenge when it comes to complying with sustainability criteria. One of the main problems currently facing aquaculture is related to the rapid accumulation of solid waste and inorganic compounds. This article thus provides an updated review of current strategies for mitigating the impact of accumulated organic and inorganic waste in closed intensive systems, such as the recirculating aquaculture system (RAS) and the use of Biofloc technology (BT), aimed at strengtheningthe aquaculture industry’s circular economy. Microorganisms’ role as bioremediation agent can be highlighted as an environmentally-appropriatetechnology, especially the action of ammonium and nitrite oxidising bacteria and photosynthetic bacteria. Incorporating bacilli and polychaeteshas been shown to be a successful strategy regarding sediment management. Successful results regarding the sustainable management of effluentshave also been obtained with multitrophic systems integrating various aquatic species having great nutritional and commercial value, such as algae,molluscs, crustaceans and echinoderms. Integrating halophytic plants from the Sarcocornia genus has been proposed regarding marine effluentsas their use has proved promising and they have been seen to have potential concerning the agricultural and biofuel industries. However, there isstill a need for further research related to using such alternative technologies on a larger scale, despite recent advances regarding their introduction,i.e. bioremediators’ mechanisms of action, valorising processes, life-cycle evaluation and their sustainability and resilience in intensive aquaculturesystems. Support between entities in the aquaculture and environmental sectors must also be strengthened to ensure a greater impact on reducingpollution and the sustainable management of natural resources.
Keywords: aquiculture; biofloc; phosphorus; organic material; nitrogen; recirculating aquaculture system; (RAS)